Produção e persistência do capim-tamani manejado com diferentes estratégias de adubação nitrogenada - Santos, Milena Alves dos (2021)
The purpose of this study was to evaluate the structural characteristics, biomass components and nitrogen use agronomic efficiency of Tamani grass managed under different nitrogen fertilization strategies. A randomized block design with four replications was adopted. The treatments were the application of a fertilizer of controlled release fractioned into one, two, four and six applications per year (FCR 1X, FCR 2X, FCR 4X and FCR 6X), conventional urea (CU) and no N fertilization (0N). Canopy height and number of new leaves per tiller showed better results in pastures managed with FCR 6X (32.80 cm and 2.60, respectively). The highest tiller population density values were observed in the treatments CU, FCR 4X and FCR 6X (1.571; 1.540 and 1.568 tillers m2, respectively). Pastures managed with FCR 4X showed increments of 28.10 and 197.76% in total accumulated forage biomass and 27.48% and 209.21% in accumulated green forage biomass when compared to pastures managed with CU and 0N, respectively. Greater accumulated green leaf blade biomass was observed in pastures managed with FCR 4X (25,561.00 kg ha-1 year-1). Pastures managed with FCR 4X and 6X showed the highest values of leaf/stem ratio. Pastures managed with FCR 4X showed higher nitrogen use agronomic efficiency (29.56 kg DM/kg N). Four or six applications of nitrogen fertilizer of controlled release positively affected canopy structural characteristics, biomass components of Tamani grass and nitrogen use agronomic efficiency.